HISTORICAL AND CULTURAL STUDIES ON MARTIAL ARTS TOURISM OF PENCA SILAT ALIRAN CIMANDE AT TARIKOLOT VILLAGE - Djunaid, Ika Suryono (APPS Publications, 2020)
Penca Silat Cimande is one form of martial arts that grows and develops traditionally in the village of Cimande, especially in the Tarikolot vilalge as it is handed down from generation to generation. This research focuses on studying the history and culture of martial arts from Cimande. This type of research is descriptive qualitative with interview guidelines and documentation as a primary data source as well as literature study as a secondary data source comprises advice of local experts and community leaders (Penca Silat organizers in Cimande, the government, and the head of Cimande village). The research concludes that, as one of the ancestral heritage objects and noble cultural values, the Penca Silat Aliran Cimande cultural arts deserves to receive better attention from the government to be able to grow and develop while maintaining the authenticity. This type of research is descriptive qualitative with interview guidelines and documentation as a primary data source and literature study as a secondary data source with 3 sources consisting of 3 parties namely organizers of the Penca Silat Cimande arts / environment organization, local government and Pokdarwis Cimande Village Keywords: tourist attraction, historical study, cultural study, martial arts, penca silat aliran cimande